الثروة السمكية في العراق الواقع و الآفاق المستقبلية - خلف, بلاسم جميل; محمد علي, سلام نعمة (Journal of Economics and Administrative Sciences, 2010)
Despite all the possibilities, owned by Iraq for the production of fish, but there is low in the level of production and in the rate of per capita consumption is due to inter alia, the weakness of investment, stop government support, a significant decline in the quantities of water, the high proportion of salinity and the proportion of pollution in the water, the use of means and fishing methods are primitive, weak laws and legislation, the policy of dumping markets imported products. Despite all this research has shown that there are investment opportunities very large in this sector through the size of the market and the absorptive capacity and the growth of per capita income and cultural revelation Strengthened the feasibility study, which was set up and gave a good indication and conducive to investment.